Translation and Adaptation of the STOPP/START Criteria Version 3 for Potentially Inappropriate Prescribing in Older People to European Portuguese: A Study Protocol - A. Rodrigues, Daniela (2024)
Introduction: As the global population ages, managing medication use in older adults becomes increasingly complex due to polypharmacy and the associated risks of adverse drug events. To improve the safety and appropriateness of medication use in the older population, tools like the Screening Tool of Older Persons’ Prescriptions (STOPP) and Screening Tool to Alert doctors to Right Treatment (START) criteria have been developed. The availability of updated criteria is crucial to better support healthcare professionals in Portuguese-speaking regions. The aim of this study is to translate and validate the STOPP/START version 3 criteria for Portuguese, providing an updated and useful tool for healthcare professionals.Methods and Analysis: This study will be conducted through four phases: I) translation of the STOPP/START version 3 criteria to European Portuguese; II) collection of sociodemographic, clinical, and medication data; III) intrarater reliability study; and IV) interrater agreement study. This study obtained ethics approval by the Ethics Committee of the Administração Regional de Saúde do Centro, Portugal. The availability of the translated criteria will enable the integration of STOPP/START version 3 into clinical practice in Portugal, facilitating improved medication safety and appropriateness. This integration is expected to lead to better management of polypharmacy and a reduction in adverse drug events, ultimately enhancing patient outcomes and supporting evidence-based prescribing practices.